Inter-Industry Wage Differentials: Evidence from Sweden and a Comparison with the United States - Edin, Per‐Anders; Zetterberg, Johnny (American Economic Review, 1992)
Inter-Industry Wage Differentials: Evidence from Sweden and a Comparison with the United States